Enhancing Medical Record Students’ Accessibility in Learning Medical Vocabulary Materials with A Web-Based Application - Yeni Nurmala Hidayati; Yudi Basuki (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
The rise of online learning during the pandemic era has changed the educational field. Through e-learning, learning is no longer limited by space and time. In response to significant demand, many free online learning platforms emerge in supporting teaching and learning in the virtual classroom. Realizing this phenomenon and based on the needs of the students, the researchers conducted a study aimed at enhancing students’ access to learning medical vocabulary materials through a web-based application, namely Wix-Site.  The research design was RD, with five steps or stages namely need analysis, studying recent theories, developing the product, validating the product to experts, and field testing the product. The subject in this study was medical records students in the first semester of the 2020/2021 academic year. The data collection method was implemented by distributing questionnaires to the students and then analyzed quantitatively. The finding of this research indicated that the implementation of the Wix-site as a means to facilitate students’ access to learning English medical vocabulary was considered effective